Sensitivity to situated positionings: Generating insight into organizational change. Issue 2 (April 2019) - Ybema, Sierk; Kamsteeg, Frans; Veldhuizen, Karlien
Within ethnographic forms of organisational research, sensitivity to context is generally acknowledged as a critical ingredient for analysing processes and practices. When conducting such research, however, researchers typically privilege one particular research context for generating knowledge: although some ethnographic scholars underscore the importance of adopting a diversity of both insider and outsider roles, ethnographic research is usually equated with gaining a deep familiarity with the field of study through immersion. First, we argue that, although immersion elicits valuable knowledge 'from within', its prioritisation inevitably blinds the researcher's eye to equally interesting insights stemming from alternative – and often unintended – positionings. Testifying to the significance of researchers' relational reflexivity for data interpretation, we show how a variety of researcher' positionings vis-à-vis the researched generated a variety of insights. Critical sensitivity to fieldworker identities in an ethnographic study of planned organisational change within a police organisation allowed us, second, to criticise the change management literature for routinely building on a fixed dichotomy between 'change agents' and 'change recipients' and to empirically demonstrate a wider variety of police officers' positionings in relation to change initiatives (i.e. countering, complying with and co-opting) and its initiators (i.e. engaging in other-depreciating, self-questioning or self-affirming identity work).